Fruit Bagging Enhances Peel Color and Affects Fruit Quality of Citrus Under Protected Screen-grown Grapefruit-like Hybrid ‘914’ - Shalini Pareek; Joseph H. Volpe; Emily S. Worbington; Arnold W. Schumann; Yuan Yu; Alma D. Hurtado; Jude W. Grosser; Fred G. Gmitter Jr; John M. Chater (HortScience)
Fruit external color is one of the primary factors associated with consumer choice at the market level. Grapefruit, pomelos, and grapefruit-like hybrids are fruits that can develop different external colors based on horticultural practices. The fruit of ‘914’, which is a grapefruit-like hybrid, is similar to grapefruit in flavor and appearance; however, it has a higher total soluble solids content. The fruit rind tends to be green-yellow to yellow with a pink blush, depending on the harvest date and site conditions. Fruit bagging is a horticultural practice that has been used for more than a century to improve the product quality and appearance of various fruit crop species. During our experiments, fruits of ‘914’ were bagged at two locations in Central Florida to determine the effects of bagging on external fruit color and internal fruit quality. Both locations had fruit-bearing trees in citrus under protected screen structures to exclude Asian citrus psyllid from the cropping system. Fruits were bagged in Jul 2023 and followed until harvest. At the Alturas, FL, USA site, there was one harvest date; however, at the Citrus Research and Education Center site, there were two harvest dates. Data trees were strip-harvested on each harvest date. Fruit weight, diameter, length, and peel color as well as total soluble solids, titratable acidity, and maturity index (soluble solids:acid) were measured. The results indicated that bagging ‘914’ positively influences external peel color and can affect internal fruit quality. More research is needed to determine the optimal windows of fruit bagging of ‘914’ grapefruit-like hybrid and the effects of bagging on consumer sensory perception and postharvest quality.